Study on the improvement of cognitive deficits in APP/PS1 mice by danggui shaoyao san and its disassembled prescriptions through modulation of the gut microbiota - Liu, Xingduo; Sun, Chaoqun; Dai, Yuqiong; Duan, Feifei; He, Tianzhen; Zhen, Menglu; Liang, Enxi; Zhang, Shuting; Xia, Yun; Hu, Nianchun; Zhan, Ruoting; Deng, Dong; et al. (Frontiers in Microbiology, 2025)
BackgroundAlzheimer’s disease (AD), a neurodegenerative disorders linked to gut microbiota dysbiosis, may benefit from Traditional Chinese Medicine (TCM) interventions.ObjectivesDanggui Shaoyao San (DSS), a classic traditional Chinese Medicine (TCM) formula. This study investigated whether Danggui Shaoyao San and its disassembled prescriptions could improve cognitive deficits in APP/PS1 mice by modulating the structure of the gut microbiota, thereby providing a theoretical basis for AD treatment and the further development and application of Danggui Shaoyao San.MethodsForty APP/PS1 and eight C57BL/6 mice were divided into six groups: DSS (6.4 g/kg/d), QDW (4.6 g/kg/d), DW (1.8 g/kg/d), GV971 (positive control, 40 mg/kg/d), model (saline), and control (saline). After 60 days of treatment, the mice underwent behavioral testing in the open field, novel object recognition, and water maze. Gut microbiota composition, diversity, and function were then analyzed by 16S rRNA sequencing.ResultsThe results of Behavioral experiment indicate that Danggui Shaoyao San and its disassembled prescriptions can ameliorate spatial memory deficits (Morris water maze), enhance recognition memory (novel object recognition), and reduce anxiety-like behaviors (open field test), with the DSS group demonstrating the most pronounced effects. In addition, through 16S sequencing analysis we predicted DSS and its disassembled prescriptions reduced harmful bacteria (Firmicutes, Akkermansia) while increasing beneficial bacteria (Bacteroidetes, Bifidobacterium, Lactobacillus). DSS restored microbial diversity closest to healthy controls, evidenced by elevated Chao1/Shannon indices and reduced Simpson index. Beta diversity revealed structural divergence between treatment and model groups. Functional predictions highlighted enriched pathways (D-glutamine metabolism, bile acid biosynthesis) and suppressed antibiotic biosynthesis.ConclusionDanggui Shaoyao San and its disassembled prescriptions ameliorate AD-related cognitive impairment and gut dysbiosis, enhance microbial diversity, and modulate metabolic pathways, supporting their therapeutic potential via gut-brain axis regulation. This study elucidates the multi-target mechanisms of DSS in AD treatment, advancing TCM rationalization for neurodegenerative disorders.